2014
DOI: 10.1123/ijsnem.2013-0169
|View full text |Cite
|
Sign up to set email alerts
|

Energy Balance, Macronutrient Intake, and Hydration Status During a 1,230 km Ultra-Endurance Bike Marathon

Abstract: Athletes competing in ultra-endurance events are advised to meet energy requirements, to supply appropriate amounts of carbohydrates (CHO), and to be adequately hydrated before and during exercise. In practice, these recommendations may not be followed because of satiety, gastrointestinal discomfort, and fatigue. The purpose of the study was to assess energy balance, macronutrient intake and hydration status before and during a 1,230-km bike marathon. A group of 14 well-trained participants (VO2max: 63.2 ± 3.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 21 publications
0
33
1
Order By: Relevance
“…This meant the subject experienced a mean energy deficit of 1992 ¡ 952 kcal/day (range: 846-3396 kcal) during the five competitive race days. Previous studies have also demonstrated that athletes were unable to consume enough food/fluid to meet estimated energy requirements during an Ironman triathlon (Kimber, Ross, Mason, & Speedy, 2002) and a 1230 km bike marathon (Geesmann, Mester, & Koehler, 2014). Despite the large negative energy deficit in the present study, the subject reported ''at no time did I feel hungry, I probably took too much food''.…”
Section: Discussioncontrasting
confidence: 47%
“…This meant the subject experienced a mean energy deficit of 1992 ¡ 952 kcal/day (range: 846-3396 kcal) during the five competitive race days. Previous studies have also demonstrated that athletes were unable to consume enough food/fluid to meet estimated energy requirements during an Ironman triathlon (Kimber, Ross, Mason, & Speedy, 2002) and a 1230 km bike marathon (Geesmann, Mester, & Koehler, 2014). Despite the large negative energy deficit in the present study, the subject reported ''at no time did I feel hungry, I probably took too much food''.…”
Section: Discussioncontrasting
confidence: 47%
“…We have previously reported dietary intake, energy expenditure, and hydration status from the same data set. 5 We chose this group of athletes because even though the athletes completed the event as a group, their energy intake, and consequently their energy balance varied considerably, 5 whereas environmental factors were identical among all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Because each athlete consumed food and beverages ad libitum, dietary intake was obtained by direct observation for each individual athlete. 5 Participants received all food and beverages from supporting staff. All food and beverages were packed individually for each athlete and were weighed to the nearest gram prior to loading the support vehicles before the start of the event.…”
Section: Energy Balancementioning
confidence: 99%
See 2 more Smart Citations